INFLUENCE OF USED LUBRICANTS TO ENVIRONMENT - Petrović, Z.; Tadić, G.; Dugić, P.; Aleksić, V.; Botić, T.; Petković, M. (Journal of Engineering & Processing Management, 2012)
In the according with very intensive application of lubricant, the very large amounts of used lubricants which are harmful to the environment and human health are produced. In the European Union countries, the problem of used lubricants are permanently solved and many directives about this problem is setted (in the starting EEC Directive 75/439 and the end 2008/98/EC). In undeveloped countries similar with Bosnia and Herzegovina there is no organized management of used lubricants yet, because we do not have adequate legislation as well as the bad environmental awareness. In due to these facts used lubricants, although treated as hazardous waste are improperly disposed near roads, streams, fields, used for burning weeds, as a fuel, for impregnating wood, etc..). These effects can be dangerous for the environment and human health. Another problem is that these lubricants are mostly poorly degradable, and some of their components are not only toxic, but carcinogenic properties. In this paper, the method of disposal of used lubricants in the municipality of Zvornik is tested. The study was conducted by interview of institutions, public companies, private companies, craft stores and citizens, and collecting statistical data. In order to study used lubricants, analysis of water and soil from selected location (near roads, companies and auto repair shops) is performed.